Parenteral nutrition versus enteral nutrition in severe acute pancreatitis - Vieira,Josiel Paiva (2010)
PURPOSE: To compare the effect of parenteral versus enteral nutritional support in severe acute pancreatitis, with respect to efficacy, safety, morbidity, mortality and length of hospitalization. METHODS: The study was comprised of 31 patients, divided into a parenteral group (n=16) and an enteral group (n=15), who met severity criteria for abdominal tomography (Balthazar classes C, D, and E). The patients were compared by demographics, disease etiology, antibiotic prophylaxis, use or not of somatostatin, nutritional support, complications and disease progression. RESULTS: There was no statistical difference in the average duration of nutritional support, somatostatin, or antibiotics in the two groups. Imipenem was the drug of choice for prophylaxis of pancreatic infections in both groups. More complications occurred in the parenteral group, although the difference was not statistically significant (p=0.10). Infectious complications, such as catheter sepsis and infections of the pancreatic tissue, were significantly more frequent in the parenteral group (p=0.006). There was no difference in average length of hospitalization in the two groups. There were three deaths in the parenteral group and none in the enteral group. CONCLUSION: Enteral nutritional support is associated with fewer septic complications compared to parenteral nutritional support.